Sensory ecologies: the refinement of movement and the senses in sport. (2nd September 2022) - Carter, Thomas F.; Heath, Sean; Jacobs, Sarah; Rana, Jasmijn
ABSTRACT: Sport is centrally concerned with the human body. Those concerns focus on how bodies move materially in space and in time. In this article, we develop our concept of "Sensory Ecology" to elucidate how one might come to develop and understand the creation of specialist bodily knowledge found in sport. Sensory ecologies are produced through the refinement of enskilled movement of bodily materials in specific spatial and temporal confines. To understand the embodied knowledge that athletes learn, it is crucial to ensure the connections between a body and its environs, the body-in-the-world affirmed via sensory interactions, and the information generated from those interactions are maintained in any research on embodiment, being-in-the-world, and the self. The body, its senses, and its surrounding environs simply cannot be separated from one another. Therefore, a sensory ecology sits in these intersectional coming-togethers of space, time, and material made manifest through the sensing of bodily movement. Throughout this article, we discuss the material of bodies and their sensing of spatialities and temporalities by arguing that our concept of "Sensory Ecology" provides a means for exploring the cultural specificities of sensing the moving and sporting body in particular and ways of being more generally.